A Inserção do psicólogo na educação básica de Sergipe : da formação à atuação profissional - Souza, Thiago Santos (2014)
In Brazil, the education was one of the first camps for professional performance of the psychologist, when these began to come out of clinical practices and crept in institutional spaces, including schools. This insertion was characterized initially by developing traditional clinical practice, whose interventions were targeted to students and, subsequently, demarcated by critical propositions which pointed to the need for a job were the school dynamics, the educational process and social interactions were the objects of intervention, taking into account the educational, cultural, social aspects, historical and institutional in the understanding of the issues. Still, among the issues related to that insertion, the education is one of the main problems, due to the fact the school and area educational be considerably neglected us undergraduate courses in psychology, not being offered, generally, subsidies and knowledge necessary for a proper practice to school context. Due to these issues the present study aimed to know the role of the psychologist in the context of basic education in the State of Sergipe, seeking to analyse the relationship between the professional performance of these with his academic training, in addition to profiling the professional school psychologists; investigate the factors that motivated the choice of this area of performance; analyze the existing conceptions about the role of the psychologist in the school context; analyze the interventions carried out; and to meet how psychologists evaluate the contributions of his academic training for your performance in education. This research had a qualitative approach, being held with 14 psychologists who work in schools or Secretariats of education in the State of Sergipe. For the collection of data was conducted semi-structured interviews, whose collected data were processed and analyzed according to Bardin's content analysis, with all due respect to the ethical standards of research. From the analysis it was possible to trace a characterization of psychologists participants, these being predominantly female, which in their majority (78.5%) work for less than four years in this area. In addition, it was found the existence of two types of conceptions concerning the role of the school psychologist, the limiting character (clinical role and problem resolver) and the facilitator character (role of partner and collaborator) to professional performance. In relation to formation was observed that 42% of psychologists evaluate positively the academic training received, claiming to have been prepared to act in the school context. Still, the models of performance identified demonstrate the existence of an initial transition from traditional practices for interventions of critical character, being a large part of these developed under the conception that the educational issues are products of social interactions that occur during the schooling process and should be directed to the various components of the institution. Finally, from the analysis, it is concluded that despite being a recent field in Sergipe, is possible to realize progress in the form of insert and conceive the role of the psychologist in the school and educational context.